Survei Pengetahuan dan Pilihan Pengobatan Jerawat di Kalangan Mahasiswa Kesehatan Universitas Jember (A Survey on Knowledge and Treatment Options of Acne Vulgaris Among Health Science Students of Universitas Jember) - Antonius Nugraha Widhi Pratama; Maulina Hari Pradipta; Afifah Machlaurin (UPT Percetakan dan Penerbitan Universitas Jember, 2017)
Acne vulgaris is a common disorder that may impact physically and psychologically. It can be treated either using appropriate self-medication or medical assistance. This present study aimed to explore the knowledge of acne vulgaris and its treatment ofchoice among health science students of Universitas Jember. Data were collected using a 44 item questionnaire. A total of 193 respondents from Faculty of Pharmacy (34 students), Faculty of Public Health (59 students), Faculty of Dentistry (27 students), Faculty of Medicine (29 students), and School of Nursing (44 students) participated in the study after giving their consents. All respondents have had acne at some points of their life. The average level of knowledge was 17.3 ± 3.6 (max score 30) and there was astatistically significant difference of means (p=0.002) among the respondents, based on their faculties. Self-medication (n=49; 58%) was more prefered than medical assistance (n=35; 41.7%). This study showed the need to increase awareness among young peopleto practice appropriate self-medication.Keywords: acne vulgaris, knowledge, treatment options